The Effects of Histamine H3 Receptors and Nitric Oxide on Electrically Stimulated Rat Ileum Contractile Responses - HEKİMOĞLU, Aşkın; ÇİÇEK, Ramazan (Cerrahpaşa Medical Journal, 2019)
The aim of the study is to determine the effects of histamine receptors on the ileum smooth muscle contractions and the role of nitric oxide on these effects. Isolated rat ileum preparations were mounted on organ bath and histamine receptor agonist and antagonists were added to the bath solution, then the electrical field stimulation-induced contractile responses were evaluated. Since NO donor Derivative 28 has H3 antagonistic effect we investigated any interaction between H3 receptors and NO. After blocking one of the histamine receptors H1, H2 and H3; contractile responses were observed. Then, other two receptors were blocked one by one or combination of them, to observe the changes on the contractile responses given to the electrical stimulation. To block histamine receptors; pyrilamine (10-6 Μ) as H1 receptor blocker, famotidine (10-6 Μ) as H2 receptor blocker and thioperamide (10-5 Μ) as H3 receptor blocker and various combination of them were used. All groups were treated with H3 receptor antagonist thioperamide (10-5 Μ) and agonist (R)-α-methylhistamine on 10-8, 10- 7, 10-6 ve 10-5 molar concentrations cumulatively, to observe its mediator effects on contractile responses. To view any possible interaction between histamine H3 receptors and nitric oxide, in the presence of nitric oxide precursore L-arginine (10-4 Μ) and nitric oxide synthase inhibitor NG-nitro-L-arginine methyl ester or combination of them the same procedures were carried out. While H1 and H2 receptor blockers decreased the contractile responses given to the electrical field stimulation, H3 receptor blocker increased the responses. Possibly, H3 receptors act contrary to H1 and H2 receptors and mediates inhibition on rat ileum smooth muscle contractility. Selective H3 agonist (R)-α-methylhistamine caused a significant inhibition on the contractile responses where these effects were abolished by selective H3 receptor antagonist thioperamide. In different series nitric oxide precursore L-arginine (10-4 Μ) and nitric oxide synthase inhibitor NG-nitro-L-arginine methyl ester (10-4 Μ) were added to the bath solution but no significant differences observed in the contractile responses. In conclusion it was observed that nitric oxide has no effect on histamine receptor mediated contractile activity in rat ileum.